Effect of Isolation Technique and Location on the Phenotype of Human Corneal Stroma-Derived Cells - Richárd Nagymihály; Zoltán Veréb; Andrea Facskó; Morten C. Moe; Goran Petrovski (Hindawi Limited, 2017)
Purpose. To determine the effect of the isolation technique and location upon the phenotype of human corneal stroma-derived cells (CSCs). Methods. CSCs were isolated from the corneal stroma center and periphery using the explant or enzymatic digestion technique. The native tissue was stained for functional markers, while cultured cells were analysed by FACS. PCR was used to determine gene expression in the cultured versus native cells. Results. The native stroma was positive for α-actinin, ALDH1A1, CD31, CD34, Collagen I, and Vimentin. Cultured cells expressed CD73, CD90, CD105, CD51, Nestin, CD49a, CD49d, ABCG2, and CD47. PCR demonstrated a significant upregulation of ALDH1A1, AQP1, ITGB4, KLF4, CD31, CD34, and CXCR4 in the native tissue, while the expression of ABCG2, ITGAV, Nestin, CD73, CD90, CD105, and Vimentin were significantly higher in the cultured cells. GPC did not change. Conclusion. The study finds no significant difference between the phenotype of CSCs generated by the explant or enzymatic digestion technique from the center or periphery of the stroma. Isolation of the cells can be performed without regard to the location and isolation technique used for research. Cultivated CSCs undergo a complete surface marker and genotype profile change compared to the state in situ.